The role of strontium on the enhancement of photocatalytic response of TiO2 nanotubes – application in methylene blue and formic acid photodegradation under visible light and UV-A. Issue 1 (31st December 2022) - Alomair, Nuhad A.
Abstract: The influence of ferroelectric strontium nanoparticles on the photocatalytic performance of 1 D TiO2 nanotubes (NT) was herein highlighted. The effect of adding various amounts of Sr nanoparticles onto NTs was therefore deeply characterized by means of Raman, UV-vis diffuse reflectance, photoluminescence (PL) and X-ray photoelectron spectroscopies, X-ray diffraction, N2 adsorption-desorption measurements and scanning electron microscopy coupled with energy-dispersive X-ray analysis as well as determining dielectric properties. The different xwt%Sr-NTs with x =(0.2, 0.4, 0.6, 0.8 and 1 wt%) were investigated for the photodegradation of Methylene Blue (MB) under visible light and formic acid under UV-A. Results emphasize that the kinetic study fits well with Langmuir-Hinshelwood (LH) model; for the same surface coverage (θ =0.99), the rate constant kLH increases versus Sr loading with an optimum at 0.8 wt% Sr. Under UV-A light, photodegradation increases versus Sr loading. As evidenced by PL, impedance and XPS measurements, the presence of ferroelectric strontium generates structural defects (Ti 3+ and Ov ) with strong opportunity to monitor the separation the photogenerated (electron- hole) pairs regardless of the synthesis limitations. Herein, the molar ratio O 2- /Ti 4+ increases vs strontium loading. Hence, Sr-NTs opens new route for "assisted" photocatalysts.